Five new species of the genus Paromphacodes (Lepidoptera: Geometridae: Geometrinae) from High Andes in Ecuador - Lindt, Aare; Tasane, Tõnis; Õunap, Erki; Viidalepp, Jaan (Zootaxa, 2017)
Four moth species are grouped in the genus Paromphacodes today. We add descriptions of further five new species: Paromphacodes alticola sp. nov., P. alpha sp. nov., P. onae sp. nov., P. spina sp. nov. and P. summita sp. nov. The species are confined to the parámo biome on summits of Andean volcanoes and were collected on five mountains. The case of the three first named species shows that the deep COI barcode splitting does not affect morphological diversification. The differentiation of P. alticola, P. alpha and P. onae is explained in association with orogeny of Andes and repeated periods of the local active volcanism.